Corporate Governance and ESG: Trends and Practices - Shibao, Fabio; Cristina da Silva, Flavia; Conceição, Márcio Magera; Gayubas, Mauricio (Journal of Sustainable Competitive Intelligence, 2024)
Purpose: This study aims to explore the integration between Corporate Governance (CG) and Environmental, Social, and Governance (ESG) practices, seeking to understand their impact on ESG indicators and corporate sustainability. It intends to highlight the relevance of CG practices aligned with ESG criteria. Methodology/approach: A systematic literature review of high-impact articles published between 2018 and 2023 was adopted, focusing on relevant CG attributes and ESG indicators. Originality/Relevance: It was identified that CG practices aligned with ESG improve sustainability indicators, highlighting the importance of gender diversity on the board and sustainability committees. Key findings: The study theoretically contributes to the CG and ESG literature, offering practical insights for implementing sustainable practices and suggesting a path to sustainability leadership. Theoretical/methodological contributions: It contributes to the theory of management and accounting, highlighting the integration between CG and ESG as essential for corporate sustainability.